Young people and spirituality: the need for a spiritual foundation for Australian schooling - Hodder, Jacqueline (International journal of children's spirituality, 2007)
The Adelaide Declaration on National Goals for Schooling in the Twenty‐First Century provides a mandate for discussion of the spiritual within secular state schooling, but this discussion has never occurred. This is a serious omission given what could be called an ‘undercurrent of concern’ for the ways in which young people today frame and make their lives in a society focused on material gain and individual pursuits. Current government policies, such as the Values Education Framework and the National School Chaplaincy Programme, hint at what could be called a spiritual approach to education, but in practice these programmes reflect government agendas tied to economistic educational goals which can be seen to be at odds with conditions that might promote propitious frameworks for young people’s wellbeing. Further, these policies fail to grasp what is at the heart of young people’s lives and inherent concerns for the kinds of lives young people are making in today’s society. A spiritual foundation for schooling has the potential to ameliorate many of these concerns, but spiritual discussions are difficult given the concept of spirituality itself is nebulous. However, I will argue in this paper that to counter the possibly detrimental effects of current cultural influences and related government policies, a spiritual foundation is needed for young Australian’s schooling.